2006
DOI: 10.1200/jco.2005.03.1161
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Intravesical Docetaxel in the Management of Superficial Bladder Cancer Refractory to Standard Intravesical Therapy

Abstract: Intravesical docetaxel exhibited minimal toxicity and no systemic absorption in the first human intravesical clinical trial. This suggests that docetaxel is a safe agent for further evaluation of efficacy in a phase II trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(72 citation statements)
references
References 32 publications
1
68
0
2
Order By: Relevance
“…139 Docetaxel, a microtubule depolymerization inhibitor, was investigated as an intravesical agent in a phase 1 trial in which docetaxel was administered with 6 weekly instillations starting at a dose of 5 mg. Eighteen (100%) patients completed the trial, and 56% of patients had no evidence of disease at their post-treatment cystoscopy and biopsy. 149 Docetaxel was well tolerated, and future trials will further evaluate its efficacy in a phase 2 trial. 149 The 2007 update of the American Urological Association (AUA) guidelines for management of nonmuscle-invasive bladder cancer states that cystectomy or further intravesical therapy may be considered for CIS or high-grade T1 cancer that persists or recurs after initial intravesical treatment.…”
Section: Nonmuscle-invasive Diseasementioning
confidence: 93%
See 1 more Smart Citation
“…139 Docetaxel, a microtubule depolymerization inhibitor, was investigated as an intravesical agent in a phase 1 trial in which docetaxel was administered with 6 weekly instillations starting at a dose of 5 mg. Eighteen (100%) patients completed the trial, and 56% of patients had no evidence of disease at their post-treatment cystoscopy and biopsy. 149 Docetaxel was well tolerated, and future trials will further evaluate its efficacy in a phase 2 trial. 149 The 2007 update of the American Urological Association (AUA) guidelines for management of nonmuscle-invasive bladder cancer states that cystectomy or further intravesical therapy may be considered for CIS or high-grade T1 cancer that persists or recurs after initial intravesical treatment.…”
Section: Nonmuscle-invasive Diseasementioning
confidence: 93%
“…149 Docetaxel was well tolerated, and future trials will further evaluate its efficacy in a phase 2 trial. 149 The 2007 update of the American Urological Association (AUA) guidelines for management of nonmuscle-invasive bladder cancer states that cystectomy or further intravesical therapy may be considered for CIS or high-grade T1 cancer that persists or recurs after initial intravesical treatment. 35 The European Association of Urology (EAU) guidelines echo this viewpoint by mentioning cystectomy as the treatment of choice for CIS patients failing adequate BCG and as an option in other high-risk tumors.…”
Section: Nonmuscle-invasive Diseasementioning
confidence: 93%
“…86 By contrast, newer nonvesicant drugs, such as gemcitabine and docetaxel, are very well tolerated. 87,88 Sequential gemcitabine-mitomycin C in 47 patients with highrisk disease, primarily after BCG failure, resulted in a complete response in 68% of patients with 1year and 2year diseasefree survival of 48% and 38%, respectively. 89 Alternatively, sequenced g emcitabine-docetaxel in 45 patients with highrisk disease yielded a complete response rate of 66%, as well as 1year and 2year recurrencefree survival of 54% and 34%, respectively.…”
Section: Consensus Statementsmentioning
confidence: 99%
“…Barlow et al, originally showed a 56% response rate in 18 patients who initially failed BCG therapy and refused to undergo cystectomy. The treatment regimen consisted of 6 weekly bladder instillations on a dose-escalation protocol (McKiernan et al, 2006) They continued their protocol, with the addition of 15 patients, for a median follow up of 29 months and had a 1 and 2 year recurrence-free survival rates of 45 and 32%. Adverse reactions to docetaxel included: dysuria, hematuria, facial flushing, frequency, rash, urinary tract infection, and premature voiding during instillation of the medication.…”
Section: Docetaxelmentioning
confidence: 99%